Multi‐scale evaluation of a linear model of orographic precipitation over Sierra de Guadarrama (Iberian Central System). (4th July 2018) - Durán, Luis; Barstad, Idar
Abstract : A linear model of orographic precipitation is validated at Sierra de Guadarrama (Iberian Central System) using ERA‐Interim as input and a historical set of precipitation data. It is the first time that a linear precipitation model is tested in a semi‐arid region like this. The historical precipitation data come from three high‐quality observatories located at the south, north and top of the mountain range. Different timescales ranging from daily, monthly and annual precipitation are analysed. Phenomena not generally taken into account in linear models like a sub‐saturated air condition and topographic mesoscale flow blocking are included in the modelling. Model results show a good agreement with observations at annual and monthly scales. The model reproduces well the high inter‐annual variability and the annual cycle, including the pronounced summer drought. Bigger differences between observed and modelled precipitations are found for some winter months and for May. Winter overestimation is attributed to measurement undersampling during snowy conditions. The underestimation in May is likely related to thermally driven convective precipitation, which is not modelled. Results also show how orographic precipitation is an important contributor to total precipitation in this area. The high‐resolution precipitation fields obtained can be used in the future for precipitation assessment and other hydrological applications. Modelled time series can also be very helpful for completing and validating the precipitation observations for the winter months. Abstract : A linear model of orographic precipitation was validated at Sierra de Guadarrama (Iberian Central System, Spain). Different timescales are analysed and phenomena like a sub‐saturated air condition and topographic mesoscale flow blocking are included. Model results show a good agreement with observations at annual and monthly scales. The model reproduces well the high inter‐annual variability and the annual cycle, including the pronounced summer drought.